2023
DOI: 10.3390/life13030692
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Integrated Use of a Dedicated Microsurgical Robot with a 4K 3D Exoscope: The Future of Microsurgery

Abstract: Innovative techniques can help overcome the limitations of the human body. Operating on very small structures requires adequate vision of the surgical field and precise movements of sophisticated instruments. Both the human eye and hand are limited when performing microsurgery. Conventional microsurgery uses operation microscopes to enhance the visualization of very small structures. Evolving technology of high-definition 3D cameras provides the opportunity to replace conventional operation microscopes, thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…With respect to area of use , there are some area and disease that micro robots can be applied. Robotics in medicine encompasses targeted drug delivery [16], surgery assistance [17], and diagnostic support [18] across various fields are shown in Table 1.…”
Section: Urological Disordersmentioning
confidence: 99%
“…With respect to area of use , there are some area and disease that micro robots can be applied. Robotics in medicine encompasses targeted drug delivery [16], surgery assistance [17], and diagnostic support [18] across various fields are shown in Table 1.…”
Section: Urological Disordersmentioning
confidence: 99%
“…However, they allowed for precise micro-movements with minimal tissue manipulation and made hard-to-reach anatomy more accessible [33] . Barbon et al demonstrated that despite a steep learning curve, the time taken for robotic anastomosis eventually became comparable to that of hand-sewn anastomosis after several procedures [35] . A significant advantage of robotic microsurgery is the ability to scale motions down from 7-20 x, allowing the robot to function at a slower, more controlled speed [33] .…”
Section: Robotic-assisted Microsurgerymentioning
confidence: 99%
“…Робот-ассистированная радикальная подкожная мастэктомия ассоциирована с низкой частотой возникновения ранних и поздних осложнений [9][10][11][12], а лимфоаксиллярная диссекция с применением методов роботической хирургии снижает вероятность возникновения послеоперационных осложнений и лимфедематозных ятрогенных осложнений [13]. Манипуляторы роботической системы позволяют оперировать в ограниченных операционном поле и полостях, поэтому их применение может сделать сложную микрохирургию более удобной [14,15]. В хирургии молочной железы роботассистированная микрохирургия также применялась в реиннервации сохраненной кожи и сосково-ареолярного комплекса.…”
Section: For Citationunclassified